2012
DOI: 10.1159/000345594
|View full text |Cite
|
Sign up to set email alerts
|

Infantile Intracranial Aggressive Fibromatosis: Report of Two Cases with a Review of the Literature

Abstract: Aggressive fibromatosis (AF) is characterized by a nonmetastatic fibroblastic proliferative lesion that is histologically benign with infiltrative growth and frequent recurrence. To our knowledge, infantile AF is rarely reported. There are no clear guidelines regarding the management and treatment strategies for intracranial infantile AF because of its rarity. In China, there are few reports in the clinical literature concerning intracranial infantile AF. We describe 2 cases of intracranial infantile AF and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Since DTF is most likely to have infiltrative growth and a tendency toward local recurrence, it is important to resect the tumor with negative margins. 3 , 11) In the cases 1–3 (reported to date) presented in Table 1 , the DTF tumors were located only at the convexity, and not the skull base. We deduced that there was no recurrence as curative resections were possible.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Since DTF is most likely to have infiltrative growth and a tendency toward local recurrence, it is important to resect the tumor with negative margins. 3 , 11) In the cases 1–3 (reported to date) presented in Table 1 , the DTF tumors were located only at the convexity, and not the skull base. We deduced that there was no recurrence as curative resections were possible.…”
Section: Discussionmentioning
confidence: 98%
“…It is reported that local recurrence rates after the first initial management range from 20% to 40%. Risk factors include the patient’s age (<37 years), large tumor size (>7 cm), and extra-abdominal or skull base tumor locations, 3 , 10) β-catenin gene ( CTNNB1 ) mutations. 6) This case had the following risk factors for recurrence: the patient was 1-year old, the tumor was large (82 mm), was located at the base of the skull base, and possibly had CTNNB1 gene mutations.…”
Section: Discussionmentioning
confidence: 99%
“…21 Furthermore, the CNS of younger children is more susceptible to the side effects of radiation and cytotoxic chemotherapy. 24 Surgery is the first-line therapy for an extraabdominal desmoid tumor when it can be accomplished without significant functional impairment. 18 Resection with histologically free margins remains an effective treatment for desmoid tumor in terms of long-term event-free survival, with a 22%-27% chance of recurrence after margin-negative resection.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, there are a few, mainly pediatric, case reports of primary intracranial DTs [64]. Next, sometimes a neurosurgical approach is needed when primary head and neck DTs affect the skull base and secondarily grow intracranially [64].…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, there are a few, mainly pediatric, case reports of primary intracranial DTs [64]. Next, sometimes a neurosurgical approach is needed when primary head and neck DTs affect the skull base and secondarily grow intracranially [64]. Furthermore, DTs can compromise the brachial or lumbosacral plexus [13], peripheral nerves [59], or the spine and/or spinal cord [55].…”
Section: Introductionmentioning
confidence: 99%